Brief, Performance-Based Cognitive Screening in Youth Aged 12–25: A Systematic Review. (19th September 2021) - Bryce, Shayden D.; Bowden, Stephen C.; Wood, Stephen J.; Allott, Kelly
Abstract: Objective: Cognitive screening is an efficient method of detecting cognitive impairment in adults and may signal need for comprehensive assessment. Cognitive screening is not, however, routinely used in youth aged 12–25, limiting clinical recommendations. The aims of this review were to describe performance-based cognitive screening tools used in people aged 12–25 and the contexts of use, review screening accuracy in detecting cognitive impairment relative to an objective reference standard, and evaluate the risk of bias of included studies. Method: Electronic databases (Scopus, Medline, PsychINFO, and ERIC) were searched for relevant studies according to pre-determined criteria. Risk of bias was rated using the Quality Assessment of Diagnostic Accuracy Studies-2. Dual screening, extraction, and quality ratings occurred at each review phase. Results: Twenty studies met the review inclusion criteria. A diverse range of screening tools (length, format) were used in youth aged 12–25 with or without health conditions. Six studies investigating cognitive screening were conducted as primary accuracy studies and reported some relevant psychometric parameters (e.g., sensitivity and specificity). Fourteen studies presented correlational data to investigate the cognitive measure utility. Studies generally presented limited data on classification accuracy, which impacted full screening tool appraisal. Risk of bias was high (or unclear) in most studies with poor adherence to the Standards for Reporting Diagnostic Accuracy Studies (STARD) criteria. Conclusions: Few, high quality studies have investigated the utility of cognitive screening in youth aged 12–25, with no screening measure emerging as superior at detecting cognitive impairment in this age group.